IDNLearn.com is your go-to platform for finding reliable answers quickly. Our platform offers comprehensive and accurate responses to help you make informed decisions on any topic.

4. Halla [tex]\( f(-3) \)[/tex]; [tex]\( f(0) \)[/tex]; [tex]\( f(m) \)[/tex]; [tex]\( f(x+1) \)[/tex]; [tex]\( f(\Delta x) \)[/tex]; [tex]\( f\left(x^2\right) \)[/tex]; [tex]\( f(x+\Delta x) \)[/tex] en cada una de las siguientes funciones:

a. [tex]\( f(x) = x^2 \)[/tex]

b. [tex]\( f(x) = x^2 - 2 \)[/tex]

c. [tex]\( f(x) = x^2 + x + 1 \)[/tex]

d. [tex]\( f(x) = x^2 \)[/tex]

e. [tex]\( f(x) = -(x+1)^2 \)[/tex]

f. [tex]\( f(x) = \frac{x^2}{2} \)[/tex]


Sagot :

Vamos a evaluar las diferentes funciones dadas para los valores especificados. Procederemos paso a paso para cada función [tex]\(f(x)\)[/tex].

### a) [tex]\(f(x) = x^2\)[/tex]

1. [tex]\(f(-3) = (-3)^2 = 9\)[/tex]
2. [tex]\(f(0) = 0^2 = 0\)[/tex]
3. [tex]\(f(m) = m^2\)[/tex]
4. [tex]\(f(x+1) = (x+1)^2 = x^2 + 2x + 1\)[/tex]
5. [tex]\(f(\Delta x) = (\Delta x)^2 = \Delta x^2\)[/tex]
6. [tex]\(f(x^2) = (x^2)^2 = x^4\)[/tex]
7. [tex]\(f(x+\Delta x) = (x + \Delta x)^2 = x^2 + 2x\Delta x + (\Delta x)^2\)[/tex]

### b) [tex]\(f(x) = x^2 - 2\)[/tex]

1. [tex]\(f(-3) = (-3)^2 - 2 = 9 - 2 = 7\)[/tex]
2. [tex]\(f(0) = 0^2 - 2 = 0 - 2 = -2\)[/tex]
3. [tex]\(f(m) = m^2 - 2\)[/tex]
4. [tex]\(f(x+1) = (x+1)^2 - 2 = x^2 + 2x + 1 - 2 = x^2 + 2x - 1\)[/tex]
5. [tex]\(f(\Delta x) = (\Delta x)^2 - 2 = \Delta x^2 - 2\)[/tex]
6. [tex]\(f(x^2) = (x^2)^2 - 2 = x^4 - 2\)[/tex]
7. [tex]\(f(x+\Delta x) = (x + \Delta x)^2 - 2 = x^2 + 2x\Delta x + (\Delta x)^2 - 2\)[/tex]

### c) [tex]\(f(x) = x^2 + x + 1\)[/tex]

1. [tex]\(f(-3) = (-3)^2 + (-3) + 1 = 9 - 3 + 1 = 7\)[/tex]
2. [tex]\(f(0) = 0^2 + 0 + 1 = 1\)[/tex]
3. [tex]\(f(m) = m^2 + m + 1\)[/tex]
4. [tex]\(f(x+1) = (x+1)^2 + (x+1) + 1 = x^2 + 2x + 1 + x + 1 + 1 = x^2 + 3x + 3\)[/tex]
5. [tex]\(f(\Delta x) = (\Delta x)^2 + \Delta x + 1 = \Delta x^2 + \Delta x + 1\)[/tex]
6. [tex]\(f(x^2) = (x^2)^2 + x^2 + 1 = x^4 + x^2 + 1\)[/tex]
7. [tex]\(f(x+\Delta x) = (x + \Delta x)^2 + (x + \Delta x) + 1 = x^2 + 2x\Delta x + (\Delta x)^2 + x + \Delta x + 1\)[/tex]

### d) [tex]\(f(x) = x^2\)[/tex]

El mismo que el caso a) porque es la misma función:

1. [tex]\(f(-3) = (-3)^2 = 9\)[/tex]
2. [tex]\(f(0) = 0^2 = 0\)[/tex]
3. [tex]\(f(m) = m^2\)[/tex]
4. [tex]\(f(x+1) = (x+1)^2 = x^2 + 2x + 1\)[/tex]
5. [tex]\(f(\Delta x) = (\Delta x)^2 = \Delta x^2\)[/tex]
6. [tex]\(f(x^2) = (x^2)^2 = x^4\)[/tex]
7. [tex]\(f(x+\Delta x) = (x + \Delta x)^2 = x^2 + 2x\Delta x + (\Delta x)^2\)[/tex]

### e) [tex]\(f(x) = -(x+1)^2\)[/tex]

1. [tex]\(f(-3) = -((-3)+1)^2 = -( -2)^2 = -4\)[/tex]
2. [tex]\(f(0) = -(0+1)^2 = -(1)^2 = -1\)[/tex]
3. [tex]\(f(m) = -(m+1)^2\)[/tex]
4. [tex]\(f(x+1) = -((x+1)+1)^2 = -(x+2)^2\)[/tex]
5. [tex]\(f(\Delta x) = -((\Delta x)+1)^2 = -(\Delta x + 1)^2\)[/tex]
6. [tex]\(f(x^2) = -(x^2 + 1)^2\)[/tex]
7. [tex]\(f(x+\Delta x) = -((x+\Delta x)+1)^2 = -(x + \Delta x + 1)^2\)[/tex]

### f) [tex]\(f(x) = \frac{x^2}{2}\)[/tex]

1. [tex]\(f(-3) = \frac{(-3)^2}{2} = \frac{9}{2}\)[/tex]
2. [tex]\(f(0) = \frac{0^2}{2} = 0\)[/tex]
3. [tex]\(f(m) = \frac{m^2}{2}\)[/tex]
4. [tex]\(f(x+1) = \frac{(x+1)^2}{2} = \frac{x^2 + 2x + 1}{2} = \frac{x^2}{2} + x + \frac{1}{2}\)[/tex]
5. [tex]\(f(\Delta x) = \frac{(\Delta x)^2}{2} = \frac{\Delta x^2}{2}\)[/tex]
6. [tex]\(f(x^2) = \frac{(x^2)^2}{2} = \frac{x^4}{2}\)[/tex]
7. [tex]\(f(x+\Delta x) = \frac{(x+\Delta x)^2}{2} = \frac{x^2 + 2x\Delta x + (\Delta x)^2}{2} = \frac{x^2}{2} + x\Delta x + \frac{\Delta x^2}{2}\)[/tex]

Estas son las evaluaciones de las funciones dadas en los puntos específicos.
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.